Nanoencapsulation of cinnamic aldehyde using zein nanofibers by novel needle-less electrospinning: Production, characterization and their application to reduce nitrite in sausages. (January 2021) - Karim, Mehri; Fathi, Milad; Soleimanian-Zad, Sabihe
Abstract: Cinnamic aldehyde is a natural antioxidant that is sensitive to humidity, oxygen, light, and high temperature. In this study, encapsulation of cinnamic aldehyde in different concentrations (10, 20, 30 and 40%) using zein nanofibers was investigated by needle-less electrospinning for large scale production. With increasing cinnamic aldehyde concentration, viscosity and electrical conductivity of solution, and diameter, encapsulation efficiency, loading capacity and antioxidant activity of nanofibers increased. Based on nanofiber morphology, encapsulation efficiency and loading capacity data, treatment with 40% cinnamic aldehyde was selected as the best sample. Release kinetics of cinnamic aldehyde were measured and mathematically modeled in saliva, gastric, intestinal and food simulated buffer media. The best models for gastric media were Kopcha and Ritger- Peppas and for saliva and intestinal media was Kopcha. Nanofibers were used for reduction of nitrite in sausages. The data showed that encapsulated cinnamic aldehyde had bactericidal effects against E. coli O157:H7 and S. aureus PTCC 1337 and did not have important adverse effect on color, texture and sensory characteristics of sausages. The results demonstrated that needle-less electrospinning can effectively encapsulate cinnamic aldehyde and preserve it from environmental conditions and the encapsulated fibers may be used for reducing of nitrite in meat products. Highlights: Zein was used to produce nanofibers containing cinnamic aldehyde by nozzle-less electrospinning. Encapsulated cinnamic aldehyde showed better antioxidant activity compared to pure cinnamic aldehyde during storage. Encapsulated cinnamic aldehyde had antibactericidal effects against E. coli O157:H7 and S. aureus PTCC 1337 without important adverse effect on color, texture profile and sensory properties of sausages.